Rynek po kryzysie. Nowe usługi post transakcyjne w odpowiedzi na rozporządzenie EMIR - Sroka, Iwona (Kwartalnik Kolegium Ekonomiczno-Społecznego. Studia i Prace, 2015)
The paper discusses the impact of Regulation (EU) No 648/2012 of the EuropeanParliament and of the Council of 4 July 2012 on OTC derivatives, central counterpartiesand trade repositories on post-trade infrastructure of the financial market.In particular, it focuses on central counterparty (CCP) clearing houses definedin the Regulation, as well as the subjective and objective scope of application ofEMIR. The paper also refers to the impact of the Regulation on the Polish market,as well as the measures taken by the local post-trade infrastructure institutions:the Central Securities Depository of Poland (KDPW) and the clearing houseKDPW_CCP.